High-strength and high-thermal-conductivity copper alloy prepared by metal powder injection molding process

By using metal powder injection molding process, combined with modifiers and binders, a high-strength and high-thermal-conductivity copper alloy was prepared, which solved the problem of insufficient performance of existing materials and realized a copper alloy material with both high strength and thermal conductivity.

CN118951020BActive Publication Date: 2025-02-18WUXI XINJUHONG INTELLIGENT TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411142720.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2025-02-18
Estimated Expiration
2044-08-20

AI Technical Summary

Technical Problem

The heat dissipation module materials used in the current optical communication field have insufficient performance. Zinc alloys have low performance, pure copper has low processing efficiency and high cost, and there is a lack of preparation schemes for high-strength and high-thermal-conductivity copper alloys.

Method used

A high-strength, high-thermal-conductivity copper alloy is prepared by using metal powder injection molding process, mixing copper powder, molybdenum powder, cobalt powder, stainless steel powder and silicon carbide powder, and combining modifiers such as mercapto-modified polyethylene glycol and carboxylated polyester.

Benefits of technology

A copper alloy with excellent comprehensive performance was prepared, which has high strength, good thermal conductivity and wear resistance, meeting the heat dissipation module requirements in the field of optical communication.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of copper alloys, specifically to a high-strength and high-thermal-conductivity copper alloy prepared based on a metal powder injection molding process. The scheme uses copper powder, molybdenum powder, cobalt powder, stainless steel powder and silicon carbide powder as a mixed powder, and modifies the surface of the mixed powder. On the one hand, the compatibility between the mixed powder and the binder is improved, so that the binder can be evenly coated on the surface of the mixed powder. On the other hand, after the surface of the mixed powder is modified, the powders interact with each other, which can improve the fluidity and powder loading capacity of the feed. Then the scheme prepares the copper alloy through an injection molding process. The copper alloy has excellent mechanical properties and hardness, and the thermal conductivity of the product is also relatively excellent, and the wear resistance is good, which meets the actual application requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of copper alloys, in particular to a high-strength and high-thermal-conductivity copper alloy prepared based on a metal powder injection molding process. Background Art

[0002] Most of the heat dissipation modules (housing) used in the existing optical communication field are manufactured by zinc alloy die-casting or pure copper machining. The zinc alloy has poor performance and can no longer meet the needs of advanced technological development. Pure copper has low processing efficiency and high cost.

[0003] In the prior art, powder metallurgy is generally used to prepare copper alloy materials, and it is rare to see a solution for preparing copper alloys by metal powder injection molding. Therefore, based on this situation, the present application discloses a high-strength and high-thermal conductivity copper alloy prepared by metal powder injection molding process, and a thermally conductive copper alloy with excellent mechanical properties and high hardness is prepared. Summary of the invention

[0004] The object of the present invention is to provide a high-strength and high-thermal-conductivity copper alloy prepared based on a metal powder injection molding process, so as to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a high-strength and high-thermal-conductivity copper alloy prepared by a metal powder injection molding process comprises the following steps:

[0006] Step (1): mixing copper powder, molybdenum powder, cobalt powder, stainless steel powder and silicon carbide powder, stirring evenly to obtain a composite powder;

[0007] Step (2): mixing the thiolated polyethylene glycol and the hydroxyl branched polyester containing a vinyl group, dissolving them in acetone, and ultrasonically dispersing them for 20 to 30 minutes to obtain a modifier;

[0008] Take the compound powder, disperse it by ultrasonic for 20-30 minutes, add the modifier, stir it at high speed at 140-150°C for 1-2 hours, the speed of high speed stirring is 800-1000 rpm, discharge it, wash and dry it to obtain powder A;

[0009] Step (3): mixing the carboxylated polyester and acetone, and stirring evenly to obtain a carboxylated polyester solution;

[0010] Take the compound powder, perform ultrasonic dispersion for 20-30 minutes, add the carboxylated polyester solution and stannous isooctanoate, stir at high speed at 130-140°C for 1-2 hours at a speed of 800-1000 rpm, discharge, wash and dry to obtain powder B;

[0011] Step (4): mixing powder A, powder B and a binder, kneading in a mixer at a mixing temperature of 150-155° C. for 2-3 hours, granulating to form feed particles, and injection molding to obtain an injection blank;

[0012] The injection blank is degreased by solvent, and then transferred to a vacuum degreasing furnace for thermal degreasing in a hydrogen atmosphere, and then transferred to a sintering furnace for sintering in a hydrogen atmosphere, and cooled in the furnace to obtain a copper alloy.

[0013] In the more optimized scheme, in step (4), during injection molding, the injection temperature is 170~175℃, and the injection pressure is 120MPa; during solvent degreasing, the solvent is n-heptane, the solvent degreasing temperature is 30~60℃, and the degreasing time is 6~10h; the thermal degreasing temperature is 600~800℃, and the thermal degreasing time is 30~60min; the sintering temperature is 1060~1080℃, and the sintering time is 2~3h; the heating rate during the above process is 3~5℃ / min.

[0014] In a more optimized solution, in step (1), the amounts of the various substances in the composite powder are as follows: in mass percentage, 0.05wt%~0.2wt% of molybdenum powder, 0.05wt%~0.3wt% of cobalt powder, 8wt%~10wt% of stainless steel powder, 5wt%~8wt% of silicon carbide powder, and the remainder is copper powder.

[0015] In a more optimized solution, in step (4), the amount of each component is: by weight, 45wt%~55wt% powder A, 5wt%~10wt% powder B, and the rest is a binder; the amount of each component of the binder is specifically: 10wt%~15wt% ethylene-vinyl acetate copolymer, 10wt%~15wt% high-density polyethylene, 3wt%~5wt% stearic acid, and the rest is paraffin;

[0016] In a more optimized solution, in step (2), the amount of the modifier is 0.5wt%~1wt% of the composite powder, and the mass ratio of the thiolated polyethylene glycol to the vinyl-containing hydroxyl branched polyester is 1:(4~5);

[0017] In step (3), the amount of the carboxylated polyester is 0.5wt% to 1wt% of the compounded powder, and the amount of stannous isooctanoate is 1 to 1.5wt% of the carboxylated polyester.

[0018] According to a more optimized scheme, the steps for preparing the vinyl-containing hydroxyl branched polyester are as follows: mixing the terminal hydroxyl hyperbranched polyester, tetrahydrofuran and triethylamine, stirring at 30-40° C. until completely dissolved, adding methacryloyl chloride, reacting at 25-30° C. for 20-24 hours, collecting the product by centrifugation, washing and drying, and obtaining the vinyl-containing hydroxyl branched polyester;

[0019] The preparation steps of the carboxylated polyester are as follows: mixing the terminal hydroxyl hyperbranched polyester, acetone and maleic anhydride, stirring evenly, adding 0.1 mL of triethylamine, reacting at 100-110° C. for 3-4 hours, collecting the product after the reaction is completed, and obtaining the carboxylated polyester.

[0020] In a more optimized solution, the molar ratio of the terminal hydroxyl hyperbranched polyester to methacryloyl chloride is 1:(5-6); the amount of triethylamine used is 1-1.2 times the mass of methacryloyl chloride; and the molar ratio of the terminal hydroxyl hyperbranched polyester to maleic anhydride is 1:(15-20).

[0021] According to a more optimized scheme, the preparation steps of the terminal hydroxyl hyperbranched polyester are as follows: polyethylene glycol and 2,2-dihydroxymethylpropionic acid are mixed, stirred evenly under a nitrogen environment, heated to 140-150° C., p-toluenesulfonic acid is added, reacted for 3-4 hours, vacuumed to remove water, and the product is collected to obtain the terminal hydroxyl hyperbranched polyester; the amount of p-toluenesulfonic acid used is 0.4wt%-0.6wt% of the total mass of the monomers; and the molar ratio of the polyethylene glycol to 2,2-dihydroxymethylpropionic acid is 1:12.

[0022] According to a more optimized scheme, the preparation steps of thiolated polyethylene glycol are as follows: polyethylene glycol and thioglycolic acid are mixed, dissolved in toluene, stirred in an oil bath at 80-85°C until the solution is clear, p-toluenesulfonic acid is added, the temperature is raised to 120-130°C, refluxed for 10-15h, the reaction solution is dropped into cold ether for precipitation, purified and washed to obtain thiolated polyethylene glycol.

[0023] In a more optimized solution, the amount of p-toluenesulfonic acid used is 3wt%~5wt% of the polyethylene glycol; the molar ratio of the thioglycolic acid to the polyethylene glycol is (1~1.2):1.

[0024] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0025] The invention discloses a high-strength and high-thermal-conductivity copper alloy prepared based on a metal powder injection molding process. The scheme uses copper powder, molybdenum powder, cobalt powder, stainless steel powder and silicon carbide powder as a mixed compound powder, and the surface of the compound powder is modified. On the one hand, the compatibility between the compound powder and the binder is improved, so that the binder can be evenly coated on the surface of the compound powder. On the other hand, after the surface of the compound powder is modified, the powders interact with each other, which can improve the fluidity and powder loading capacity of the feed. Then the scheme prepares the copper alloy through an injection molding process. The copper alloy has excellent mechanical properties and hardness, and the thermal conductivity of the product is also relatively excellent, and the wear resistance is good, which meets the actual application requirements.

[0026] The scheme mixes copper powder, molybdenum powder, cobalt powder, stainless steel powder and silicon carbide powder, with copper powder as the main component to ensure the thermal conductivity and electrical conductivity of the material; the introduction of stainless steel powder is to improve the corrosion resistance of the copper alloy, while the introduction of silicon carbide powder can improve the mechanical properties and surface wear resistance of the copper alloy. Therefore, the compound powder is used as the raw material for injection molding, and the scheme selects a paraffin-based binder system, compounding ethylene-vinyl acetate copolymer, high-density polyethylene, stearic acid and paraffin as a binder, and finally a copper alloy with excellent comprehensive performance can be produced.

[0027] On the basis of this scheme, the present application performs surface modification on the composite powder. First, a mixture of a hydroxyl branched polyester containing vinyl groups and a thiolated polyethylene glycol is used as a modifier to perform surface modification on the composite powder to obtain powder A. The hydroxyl branched polyester containing vinyl groups is obtained by reacting a terminal hydroxyl hyperbranched polyester with methacryloyl chloride. The substance contains a large number of hydroxyl groups and vinyl groups. The introduction of vinyl groups can effectively improve the compatibility of the composite powder with the binder. The thiolated polyethylene glycol has a small molecular weight, and the thiol group interacts with the metal powder, which can improve the modification effect. The uniform and fine capillary channels formed during the subsequent degreasing improve the stability of the product.

[0028] On the other hand, the scheme uses carboxylated polyester to modify the surface of the compound powder to obtain powder B. In the subsequent preparation process, the groups on the surfaces of powders A and B can interact with each other, making the powders closer, the binder can be more evenly coated on the surface of the raw powder, and the compatibility between the compound powder and the binder is better. The final product has better comprehensive mechanics and higher dimensional stability. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In this embodiment, the molecular weight of polyethylene glycol is 400; the copper powder is pure copper powder, the molybdenum powder is pure molybdenum powder, and the cobalt powder is pure cobalt powder, all with a particle size of 20 μm; the silicon carbide powder has a particle size of 10 μm; and the stainless steel powder is 316L stainless steel with a particle size of 12 μm.

[0031] The preparation steps of thiolated polyethylene glycol are as follows: polyethylene glycol and thioglycolic acid are mixed, toluene is dissolved, stirring is performed in an oil bath at 85°C until the solution is clear, p-toluenesulfonic acid is added, the temperature is raised to 125°C, reflux reaction is performed for 12 hours, the reaction solution is dropped into cold ether for precipitation, purified and washed, and thiolated polyethylene glycol is obtained. The amount of p-toluenesulfonic acid used is 4wt% of polyethylene glycol; the molar ratio of thioglycolic acid to polyethylene glycol is 1.1:1.

[0032] The preparation steps of the terminal hydroxyl hyperbranched polyester are as follows: polyethylene glycol and 2,2-dihydroxymethyl propionic acid are mixed, stirred evenly under a nitrogen environment, heated to 145° C., p-toluenesulfonic acid is added, reacted for 4 hours, vacuumed to remove water, and the product is collected to obtain the terminal hydroxyl hyperbranched polyester; the amount of p-toluenesulfonic acid used is 0.5wt% of the total weight of the monomers; and the molar ratio of the polyethylene glycol to the 2,2-dihydroxymethyl propionic acid is 1:12.

[0033] Embodiment 1: A high-strength and high-thermal-conductivity copper alloy prepared by a metal powder injection molding process comprises the following steps:

[0034] Step (1): copper powder, molybdenum powder, cobalt powder, stainless steel powder and silicon carbide powder are mixed and stirred to obtain a composite powder; in terms of mass percentage, the molybdenum powder is 0.1wt%, the cobalt powder is 0.15wt%, the stainless steel powder is 8wt%, the silicon carbide powder is 6wt%, and the balance is copper powder.

[0035] Step (2): Mix the thiolated polyethylene glycol and the hydroxyl branched polyester containing vinyl groups, dissolve them in acetone, and ultrasonically disperse them for 20 minutes to obtain a modifier; the mass ratio of the thiolated polyethylene glycol to the hydroxyl branched polyester containing vinyl groups is 1:4.

[0036] The composite powder was taken, ultrasonically dispersed for 20 minutes, a modifier was added, and high-speed stirring was performed at 140° C. for 2 hours at a speed of 800 rpm. The material was discharged, washed, and dried to obtain powder A; the amount of the modifier used was 0.5 wt% of the composite powder.

[0037] Step (3): mixing the carboxylated polyester and acetone, and stirring evenly to obtain a carboxylated polyester solution;

[0038] The composite powder was ultrasonically dispersed for 20 min, the carboxylated polyester solution and stannous isooctanoate were added, and the mixture was stirred at high speed for 2 h at 130° C. The rotation speed during high-speed stirring was 900 rpm. The powder was discharged, washed and dried to obtain powder B; the amount of the carboxylated polyester was 0.5 wt% of the composite powder, and the amount of stannous isooctanoate was 1.2 wt% of the carboxylated polyester.

[0039] Step (4): 55 wt% of powder A, 10 wt% of powder B and 35 wt% of a binder are mixed, kneaded in a mixer at a mixing temperature of 155° C. for 2.5 h, granulated to form feed particles, and injection molded at an injection temperature of 175° C. and an injection pressure of 120 MPa to obtain an injection blank; the specific amounts of the binder components are: 15 wt% of ethylene-vinyl acetate copolymer, 15 wt% of high-density polyethylene, 5 wt% of stearic acid, and the remainder is paraffin.

[0040] The injection blank was degreased by solvent, the solvent was n-heptane, the solvent degreasing temperature was 50℃, and the degreasing time was 8h; then it was transferred to a vacuum degreasing furnace, and hot degreasing was performed under a hydrogen atmosphere, the hot degreasing temperature was 700℃, and the hot degreasing time was 50min; then it was transferred to a sintering furnace, sintered under a hydrogen atmosphere, the sintering temperature was 1060℃, and the sintering time was 2.5h, and cooled with the furnace to obtain a copper alloy. The heating rate during the above process was 5℃ / min.

[0041] The preparation method of the hydroxyl branched polyester containing vinyl groups is as follows: 4 mmol of terminal hydroxyl hyperbranched polyester, 100 mL of tetrahydrofuran and triethylamine are mixed, stirred at 30°C until completely dissolved, 22 mmol of methacryloyl chloride is added, reacted at 25°C for 24 hours, the product is collected by centrifugation, washed and dried to obtain the hydroxyl branched polyester containing vinyl groups. The molar ratio of the terminal hydroxyl hyperbranched polyester to methacryloyl chloride is 1:5.5; the amount of triethylamine used is 1.2 times the mass of methacryloyl chloride.

[0042] The preparation method of the carboxylated polyester is as follows: 1 mmol of terminal hydroxyl hyperbranched polyester, 50 mL of acetone and 16 mmol of maleic anhydride are mixed, stirred evenly, 0.1 mL of triethylamine is added, and the mixture is reacted at 100° C. for 4 hours. After the reaction is completed, the product is collected to obtain the carboxylated polyester; the molar ratio of the terminal hydroxyl hyperbranched polyester to the maleic anhydride is 1:16.

[0043] Embodiment 2: A high-strength and high-thermal-conductivity copper alloy prepared by a metal powder injection molding process comprises the following steps:

[0044] Step (1): copper powder, molybdenum powder, cobalt powder, stainless steel powder and silicon carbide powder are mixed and stirred evenly to obtain a composite powder; in terms of mass percentage, the molybdenum powder is 0.1wt%, the cobalt powder is 0.15wt%, the stainless steel powder is 9wt%, the silicon carbide powder is 7wt%, and the balance is copper powder.

[0045] Step (2): Mix the thiolated polyethylene glycol and the hydroxyl branched polyester containing vinyl groups, dissolve them in acetone, and ultrasonically disperse them for 25 minutes to obtain a modifier; the mass ratio of the thiolated polyethylene glycol to the hydroxyl branched polyester containing vinyl groups is 1:4.

[0046] The composite powder was taken, ultrasonically dispersed for 25 minutes, a modifier was added, and high-speed stirring was performed at 145° C. for 1.5 hours at a speed of 800 rpm. The powder was discharged, washed, and dried to obtain powder A; the amount of the modifier was 0.5 wt% of the composite powder.

[0047] Step (3): mixing the carboxylated polyester and acetone, and stirring evenly to obtain a carboxylated polyester solution;

[0048] The composite powder was ultrasonically dispersed for 25 min, the carboxylated polyester solution and stannous isooctanoate were added, and the mixture was stirred at high speed at 135° C. for 1.5 h at a speed of 900 rpm. The powder was discharged, washed and dried to obtain powder B; the amount of the carboxylated polyester was 0.5 wt% of the composite powder, and the amount of stannous isooctanoate was 1.2 wt% of the carboxylated polyester.

[0049] Step (4): 55 wt% of powder A, 10 wt% of powder B and 35 wt% of a binder are mixed, kneaded in a mixer at a mixing temperature of 155° C. for 2.5 h, granulated to form feed particles, and injection molded at an injection temperature of 175° C. and an injection pressure of 120 MPa to obtain an injection blank; the specific amounts of the binder components are: 15 wt% of ethylene-vinyl acetate copolymer, 15 wt% of high-density polyethylene, 5 wt% of stearic acid, and the remainder is paraffin.

[0050] The injection blank was degreased by solvent, the solvent was n-heptane, the solvent degreasing temperature was 50℃, and the degreasing time was 8h; then it was transferred to a vacuum degreasing furnace, and hot degreasing was performed under a hydrogen atmosphere, the hot degreasing temperature was 700℃, and the hot degreasing time was 50min; then it was transferred to a sintering furnace, sintered under a hydrogen atmosphere, the sintering temperature was 1060℃, and the sintering time was 2.5h, and cooled with the furnace to obtain a copper alloy. The heating rate during the above process was 5℃ / min.

[0051] The preparation method of the hydroxyl branched polyester containing vinyl is as follows: 4mmol of terminal hydroxyl hyperbranched polyester, 100mL of tetrahydrofuran and triethylamine are mixed, stirred at 35°C until completely dissolved, 22mmol of methacryloyl chloride is added, reacted at 30°C for 22h, the product is collected by centrifugation, washed and dried to obtain the hydroxyl branched polyester containing vinyl. The molar ratio of terminal hydroxyl hyperbranched polyester to methacryloyl chloride is 1:5.5; the amount of triethylamine used is 1.2 times the mass of methacryloyl chloride.

[0052] The preparation method of the carboxylated polyester is as follows: 1 mmol of terminal hydroxyl hyperbranched polyester, 50 mL of acetone and 16 mmol of maleic anhydride are mixed, stirred evenly, 0.1 mL of triethylamine is added, and the mixture is reacted at 105° C. for 3.5 hours. After the reaction is completed, the product is collected to obtain the carboxylated polyester; the molar ratio of the terminal hydroxyl hyperbranched polyester to the maleic anhydride is 1:16.

[0053] Embodiment 3: A high-strength and high-thermal-conductivity copper alloy prepared by a metal powder injection molding process comprises the following steps:

[0054] Step (1): copper powder, molybdenum powder, cobalt powder, stainless steel powder and silicon carbide powder are mixed and stirred evenly to obtain a composite powder; in terms of mass percentage, the molybdenum powder is 0.1wt%, the cobalt powder is 0.15wt%, the stainless steel powder is 10wt%, the silicon carbide powder is 8wt%, and the balance is copper powder.

[0055] Step (2): Mix the thiolated polyethylene glycol and the hydroxyl branched polyester containing vinyl groups, dissolve them in acetone, and ultrasonically disperse them for 30 minutes to obtain a modifier; the mass ratio of the thiolated polyethylene glycol to the hydroxyl branched polyester containing vinyl groups is 1:4.

[0056] The composite powder was taken, ultrasonically dispersed for 30 minutes, a modifier was added, and high-speed stirring was performed at 150° C. for 1 hour at a speed of 800 rpm. The material was discharged, washed, and dried to obtain powder A; the amount of the modifier used was 0.5 wt% of the composite powder.

[0057] Step (3): mixing the carboxylated polyester and acetone, and stirring evenly to obtain a carboxylated polyester solution;

[0058] The composite powder was ultrasonically dispersed for 30 min, the carboxylated polyester solution and stannous isooctanoate were added, and the mixture was stirred at high speed at 140°C for 1 h at a speed of 900 rpm. The powder was discharged, washed and dried to obtain powder B; the amount of the carboxylated polyester was 0.5 wt% of the composite powder, and the amount of stannous isooctanoate was 1.2 wt% of the carboxylated polyester.

[0059] Step (4): 55 wt% of powder A, 10 wt% of powder B and 35 wt% of a binder are mixed, kneaded in a mixer at a mixing temperature of 155° C. for 2.5 h, granulated to form feed particles, and injection molded at an injection temperature of 175° C. and an injection pressure of 120 MPa to obtain an injection blank; the specific amounts of the binder components are: 15 wt% of ethylene-vinyl acetate copolymer, 15 wt% of high-density polyethylene, 5 wt% of stearic acid, and the remainder is paraffin.

[0060] The injection blank was degreased by solvent, the solvent was n-heptane, the solvent degreasing temperature was 50℃, and the degreasing time was 8h; then it was transferred to a vacuum degreasing furnace, and hot degreasing was performed under a hydrogen atmosphere, the hot degreasing temperature was 700℃, and the hot degreasing time was 50min; then it was transferred to a sintering furnace, sintered under a hydrogen atmosphere, the sintering temperature was 1060℃, and the sintering time was 2.5h, and cooled with the furnace to obtain a copper alloy. The heating rate during the above process was 5℃ / min.

[0061] The preparation method of the hydroxyl branched polyester containing vinyl groups is as follows: 4 mmol of terminal hydroxyl hyperbranched polyester, 100 mL of tetrahydrofuran and triethylamine are mixed, stirred at 40°C until completely dissolved, 22 mmol of methacryloyl chloride is added, reacted at 30°C for 20 hours, the product is collected by centrifugation, washed and dried to obtain the hydroxyl branched polyester containing vinyl groups. The molar ratio of the terminal hydroxyl hyperbranched polyester to methacryloyl chloride is 1:5.5; the amount of triethylamine used is 1.2 times the mass of methacryloyl chloride.

[0062] The preparation method of the carboxylated polyester is as follows: 1 mmol of terminal hydroxyl hyperbranched polyester, 50 mL of acetone and 16 mmol of maleic anhydride are mixed, stirred evenly, 0.1 mL of triethylamine is added, and the mixture is reacted at 110° C. for 3 hours. After the reaction is completed, the product is collected to obtain the carboxylated polyester; the molar ratio of the terminal hydroxyl hyperbranched polyester to the maleic anhydride is 1:16.

[0063] Comparative Example 1: Example 3 was used as the control group. Silicon carbide powder was not introduced into Comparative Example 1, and the other steps remained unchanged.

[0064] The high-strength and high-thermal-conductivity copper alloy prepared by the metal powder injection molding process includes the following steps:

[0065] Step (1): copper powder, molybdenum powder, cobalt powder and stainless steel powder are mixed and stirred evenly to obtain a composite powder; in terms of mass percentage, the molybdenum powder is 0.1wt%, the cobalt powder is 0.15wt%, the stainless steel powder is 10wt%, and the balance is copper powder.

[0066] Steps (2) to (4) are consistent with those in Example 3.

[0067] Comparative Example 2: Example 3 was used as the control group. In Comparative Example 2, thiolated polyethylene glycol was not introduced, and the other steps remained unchanged.

[0068] The high-strength and high-thermal-conductivity copper alloy prepared by the metal powder injection molding process includes the following steps:

[0069] Step (1): copper powder, molybdenum powder, cobalt powder, stainless steel powder and silicon carbide powder are mixed and stirred evenly to obtain a composite powder; in terms of mass percentage, the molybdenum powder is 0.1wt%, the cobalt powder is 0.15wt%, the stainless steel powder is 10wt%, the silicon carbide powder is 8wt%, and the balance is copper powder.

[0070] Step (2): dissolving the vinyl-containing hydroxyl branched polyester in acetone and dispersing it by ultrasonication for 30 minutes to obtain a modifier.

[0071] The composite powder was taken, ultrasonically dispersed for 30 minutes, a modifier was added, and high-speed stirring was performed at 150° C. for 1 hour at a speed of 800 rpm. The material was discharged, washed, and dried to obtain powder A; the amount of the modifier used was 0.5 wt% of the composite powder.

[0072] Steps (3) to (4) are consistent with those in Example 3.

[0073] Comparative Example 3: Example 3 was used as a control group. In Comparative Example 3, the surface modification was not performed by carboxylating the polyester, and the other steps remained unchanged.

[0074] The high-strength and high-thermal-conductivity copper alloy prepared by the metal powder injection molding process includes the following steps:

[0075] Step (1): copper powder, molybdenum powder, cobalt powder, stainless steel powder and silicon carbide powder are mixed and stirred evenly to obtain a composite powder; in terms of mass percentage, the molybdenum powder is 0.1wt%, the cobalt powder is 0.15wt%, the stainless steel powder is 10wt%, the silicon carbide powder is 8wt%, and the balance is copper powder.

[0076] Step (2): Mix the thiolated polyethylene glycol and the hydroxyl branched polyester containing vinyl groups, dissolve them in acetone, and ultrasonically disperse them for 30 minutes to obtain a modifier; the mass ratio of the thiolated polyethylene glycol to the hydroxyl branched polyester containing vinyl groups is 1:4.

[0077] The composite powder was taken, ultrasonically dispersed for 30 minutes, a modifier was added, and high-speed stirring was performed at 150° C. for 1 hour at a speed of 800 rpm. The material was discharged, washed, and dried to obtain powder A; the amount of the modifier used was 0.5 wt% of the composite powder.

[0078] Step (3): 65 wt% of powder A and 35 wt% of a binder are mixed, kneaded in a mixer at a mixing temperature of 155° C. for 2.5 h, granulated to form feed particles, and injection molded at an injection temperature of 175° C. and an injection pressure of 120 MPa to obtain an injection blank; the specific amounts of the binder components are: 15 wt% ethylene-vinyl acetate copolymer, 15 wt% high-density polyethylene, 5 wt% stearic acid, and the remainder paraffin.

[0079] The injection blank was degreased by solvent, the solvent was n-heptane, the solvent degreasing temperature was 50℃, and the degreasing time was 8h; then it was transferred to a vacuum degreasing furnace, and hot degreasing was performed under a hydrogen atmosphere, the hot degreasing temperature was 700℃, and the hot degreasing time was 50min; then it was transferred to a sintering furnace, sintered under a hydrogen atmosphere, the sintering temperature was 1060℃, and the sintering time was 2.5h, and cooled with the furnace to obtain a copper alloy. The heating rate during the above process was 5℃ / min.

[0080] The preparation method of the hydroxyl branched polyester containing vinyl groups is as follows: 4 mmol of terminal hydroxyl hyperbranched polyester, 100 mL of tetrahydrofuran and triethylamine are mixed, stirred at 40°C until completely dissolved, 22 mmol of methacryloyl chloride is added, reacted at 30°C for 20 hours, the product is collected by centrifugation, washed and dried to obtain the hydroxyl branched polyester containing vinyl groups. The molar ratio of the terminal hydroxyl hyperbranched polyester to methacryloyl chloride is 1:5.5; the amount of triethylamine used is 1.2 times the mass of methacryloyl chloride.

[0081] Comparative Example 4: Example 3 was used as the control group. In Comparative Example 4, surface modification was performed only by using terminal hydroxyl hyperbranched polyester, and the other steps remained unchanged.

[0082] The high-strength and high-thermal-conductivity copper alloy prepared by the metal powder injection molding process includes the following steps:

[0083] Step (1): copper powder, molybdenum powder, cobalt powder, stainless steel powder and silicon carbide powder are mixed and stirred evenly to obtain a composite powder; in terms of mass percentage, the molybdenum powder is 0.1wt%, the cobalt powder is 0.15wt%, the stainless steel powder is 10wt%, the silicon carbide powder is 8wt%, and the balance is copper powder.

[0084] Step (2): dissolving the terminal hydroxyl hyperbranched polyester in acetone and ultrasonically dispersing it for 30 minutes to obtain a modifier.

[0085] The composite powder was taken, ultrasonically dispersed for 30 minutes, a modifier was added, and high-speed stirring was performed at 150° C. for 1 hour at a speed of 800 rpm. The material was discharged, washed, and dried to obtain powder A; the amount of the modifier used was 0.5 wt% of the composite powder.

[0086] Step (3): 65 wt% of powder A and 35 wt% of a binder are mixed, kneaded in a mixer at a mixing temperature of 155° C. for 2.5 h, granulated to form feed particles, and injection molded at an injection temperature of 175° C. and an injection pressure of 120 MPa to obtain an injection blank; the specific amounts of the binder components are: 15 wt% of ethylene-vinyl acetate copolymer, 15 wt% of high-density polyethylene, 5 wt% of stearic acid, and the remainder is paraffin.

[0087] The injection blank was degreased by solvent, the solvent was n-heptane, the solvent degreasing temperature was 50℃, and the degreasing time was 8h; then it was transferred to a vacuum degreasing furnace, and hot degreasing was performed under a hydrogen atmosphere, the hot degreasing temperature was 700℃, and the hot degreasing time was 50min; then it was transferred to a sintering furnace, sintered under a hydrogen atmosphere, the sintering temperature was 1060℃, and the sintering time was 2.5h, and cooled with the furnace to obtain a copper alloy. The heating rate during the above process was 5℃ / min.

[0088] The preparation method of the hydroxyl branched polyester containing vinyl groups is as follows: 4 mmol of terminal hydroxyl hyperbranched polyester, 100 mL of tetrahydrofuran and triethylamine are mixed, stirred at 40°C until completely dissolved, 22 mmol of methacryloyl chloride is added, reacted at 30°C for 20 hours, the product is collected by centrifugation, washed and dried to obtain the hydroxyl branched polyester containing vinyl groups. The molar ratio of the terminal hydroxyl hyperbranched polyester to methacryloyl chloride is 1:5.5; the amount of triethylamine used is 1.2 times the mass of methacryloyl chloride.

[0089] The preparation method of the carboxylated polyester is as follows: 1 mmol of terminal hydroxyl hyperbranched polyester, 50 mL of acetone and 16 mmol of maleic anhydride are mixed, stirred evenly, 0.1 mL of triethylamine is added, and the mixture is reacted at 110° C. for 3 hours. After the reaction is completed, the product is collected to obtain the carboxylated polyester; the molar ratio of the terminal hydroxyl hyperbranched polyester to the maleic anhydride is 1:16.

[0090] Detection experiment:

[0091] 1. Take the copper alloy samples prepared in Examples 1 to 3 and Comparative Examples 1 to 4, and measure the hardness of the samples using a Rockwell hardness tester. During the test, take 5 to 6 test sites and take the average value. The load is 150 kg and the loading time is 5 s. Test the thermal conductivity of the copper alloy samples. Test the flexural strength of the samples using an electronic universal testing machine. The sample size is 50×8×5 mm and the loading rate is 0.5 mm / min.

[0092] 2. According to the methods disclosed in Examples 1 to 3 and Comparative Examples 1 to 4, the dumbbell-shaped specimens of the samples were tested for length changes before and after thermal degreasing, and the length change rate was calculated.

[0093]

[0094] Conclusion: The copper alloy has excellent mechanical properties and hardness, and the product also has excellent thermal conductivity and good wear resistance, which meets the actual application requirements.

[0095] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high-strength and high-thermal-conductivity copper alloy prepared by metal powder injection molding process, characterized in that: The specific preparation steps of high thermal conductivity copper alloy are: Step (1): mixing copper powder, molybdenum powder, cobalt powder, stainless steel powder and silicon carbide powder, stirring evenly to obtain a composite powder; Step (2): mixing the thiolated polyethylene glycol and the hydroxyl branched polyester containing a vinyl group, dissolving them in acetone, and ultrasonically dispersing them for 20 to 30 minutes to obtain a modifier; The composite powder prepared in step (1) is subjected to ultrasonic dispersion for 20 to 30 minutes, a modifier is added, and the mixture is stirred at high speed at 140 to 150° C. for 1 to 2 hours at a speed of 800 to 1000 rpm. The mixture is discharged, washed, and dried to obtain powder A; the amount of the modifier is 0.5 wt% to 1 wt% of the composite powder, and the mass ratio of the thiolated polyethylene glycol to the vinyl-containing hydroxyl branched polyester is 1:(4 to 5); Step (3): mixing the carboxylated polyester and acetone, and stirring evenly to obtain a carboxylated polyester solution; The composite powder prepared in step (1) is subjected to ultrasonic dispersion for 20 to 30 minutes, and then the carboxylated polyester solution and stannous isooctanoate are added, and the mixture is stirred at high speed at 130 to 140° C. for 1 to 2 hours at a speed of 800 to 1000 rpm. The mixture is discharged, washed, and dried to obtain powder B; the amount of the carboxylated polyester is 0.5 wt% to 1 wt% of the composite powder, and the amount of the stannous isooctanoate is 1 to 1.5 wt% of the carboxylated polyester; Step (4): mixing powder A, powder B and a binder, kneading in a mixer at a mixing temperature of 150-155° C. for 2-3 hours, granulating to form feed particles, and injection molding to obtain an injection blank; The injection blank is degreased by solvent, and then transferred to a vacuum degreasing furnace for thermal degreasing in a hydrogen atmosphere, and then transferred to a sintering furnace for sintering in a hydrogen atmosphere, and cooled in the furnace to obtain a copper alloy.

2. The high-strength and high-thermal-conductivity copper alloy prepared by the metal powder injection molding process according to claim 1, characterized in that: In step (4), during injection molding, the injection temperature is 170~175°C and the injection pressure is 120MPa; during solvent degreasing, the solvent is n-heptane, the solvent degreasing temperature is 30~60°C, and the degreasing time is 6~10h; the thermal degreasing temperature is 600~800°C, and the thermal degreasing time is 30~60min; the sintering temperature is 1060~1080°C, and the sintering time is 2~3h; the heating rate during the above process is 3~5°C / min.

3. The high-strength and high-thermal-conductivity copper alloy prepared by the metal powder injection molding process according to claim 1, characterized in that: In step (1), the amounts of the various substances in the composite powder are as follows: in mass percentage, 0.05wt%~0.2wt% of molybdenum powder, 0.05wt%~0.3wt% of cobalt powder, 8wt%~10wt% of stainless steel powder, 5wt%~8wt% of silicon carbide powder, and the remainder is copper powder.

4. The high-strength and high-thermal-conductivity copper alloy prepared by the metal powder injection molding process according to claim 1, characterized in that: In step (4), the amount of each component is: by mass, 45wt%~55wt% powder A, 5wt%~10wt% powder B, and the rest is a binder; the amount of each component of the binder is specifically: ethylene-vinyl acetate copolymer 10wt%~15wt%, high-density polyethylene 10wt%~15wt%, stearic acid 3wt%~5wt%, and the rest is paraffin.

5. The high-strength and high-thermal-conductivity copper alloy prepared by the metal powder injection molding process according to claim 1, characterized in that: The preparation steps of the vinyl-containing hydroxyl branched polyester are as follows: mixing terminal hydroxyl hyperbranched polyester, tetrahydrofuran and triethylamine, stirring at 30-40° C. until completely dissolved, adding methacryloyl chloride, reacting at 25-30° C. for 20-24 hours, collecting the product by centrifugation, washing and drying, and obtaining the vinyl-containing hydroxyl branched polyester; The preparation steps of the carboxylated polyester are as follows: mixing the terminal hydroxyl hyperbranched polyester, acetone and maleic anhydride, stirring evenly, adding 0.1 mL of triethylamine, reacting at 100-110° C. for 3-4 hours, collecting the product after the reaction is completed, and obtaining the carboxylated polyester.

6. The high-strength and high-thermal-conductivity copper alloy prepared by the metal powder injection molding process according to claim 5, characterized in that: The molar ratio of the terminal hydroxyl hyperbranched polyester to methacryloyl chloride is 1:(5-6); the amount of triethylamine used is 1-1.2 times the mass of methacryloyl chloride; and the molar ratio of the terminal hydroxyl hyperbranched polyester to maleic anhydride is 1:(15-20).

7. The high-strength and high-thermal-conductivity copper alloy prepared by the metal powder injection molding process according to claim 6, characterized in that: The preparation steps of the terminal hydroxyl hyperbranched polyester are as follows: polyethylene glycol and 2,2-dihydroxymethyl propionic acid are mixed, stirred evenly under a nitrogen environment, heated to 140-150° C., p-toluenesulfonic acid is added, reacted for 3-4 hours, vacuumed to remove water, and the product is collected to obtain the terminal hydroxyl hyperbranched polyester; the amount of p-toluenesulfonic acid used is 0.4wt%-0.6wt% of the total weight of the monomers; and the molar ratio of the polyethylene glycol to the 2,2-dihydroxymethyl propionic acid is 1:

12.

8. The high-strength and high-thermal-conductivity copper alloy prepared by the metal powder injection molding process according to claim 1, characterized in that: The preparation steps of thiolated polyethylene glycol are as follows: polyethylene glycol and thioglycolic acid are mixed, dissolved in toluene, stirred in an oil bath at 80-85° C. until the solution is clear, p-toluenesulfonic acid is added, the temperature is raised to 120-130° C., refluxed for 10-15 hours, the reaction solution is dropped into cold ether for precipitation, purified and washed to obtain thiolated polyethylene glycol.

9. The high-strength and high-thermal-conductivity copper alloy prepared by the metal powder injection molding process according to claim 8, characterized in that: The amount of p-toluenesulfonic acid used is 3wt%~5wt% of the polyethylene glycol; the molar ratio of the thioglycolic acid to the polyethylene glycol is (1~1.2):1.

Citation Information

Patent Citations

  • High-thermal-conductivity injection molding feed containing titanium-stainless steel composite powder as well as preparation method and application of high-thermal-conductivity injection molding feed

    CN117340252A

  • Powder injection molding silicon carbide copper composite material and preparation method thereof

    CN118106491A